Polyunsaturated fatty acid analogues differentially affect cardiac Na(V), Ca(V), and K(V) channels through unique mechanisms - Bohannon, Briana M (eLife, 2020)
The cardiac ventricular action potential depends on several voltage-gated ion channels, including Na(V), Ca(V), and K(V) channels. Mutations in these channels can cause Long QT Syndrome (LQTS) which increases the risk for ventricular fibrillation and sudden cardiac death. Polyunsaturated fatty acids (PUFAs) have emerged as potential therapeutics for LQTS because they are modulators of voltage-gated ion channels. Here we demonstrate that PUFA analogues vary in their selectivity for human voltage-gated ion channels involved in the ventricular action potential. The effects of specific PUFA analogues range from selective for a specific ion channel to broadly modulating cardiac ion channels from all three families (Na(V), Ca(V), and K(V)). In addition, a PUFA analogue selective for the cardiac I(Ks) channel (Kv7.1/KCNE1) is effective in shortening the cardiac action potential in human-induced pluripotent stem cell-derived cardiomyocytes. Our data suggest that PUFA analogues could potentially be developed as therapeutics for LQTS and cardiac arrhythmia.